Analisis Persediaan Pakan Ikan Pada UD. Alisandra Jaya Abadi Di Loa Kulu - Anggareni, Aji Desilia; Juanda, Rendy; Novita, Siska (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2019)
Abstract:The purpose of this research is to analyze the inventory of fish feed on UD.Alisandra Jaya Abadi addressed on JL. Jendral sudirman subdistrict Loa Kulu.The owner of a company is Mr. Ismail and the head of the company (manager) named Mrs. Ismawati.Problems that appeared then was about the level of preparation of fish feed that is experiencing an excess or shortage of supplies at a certain period in UD.Alisandra Jaya Abadi in Loa Kulu. Company that became a distributor of fish and feed the fish and have a lot of agents and partners breeders make this company is required to be able to guarantee the availability of fish feed at any time.Fish feed primarily on the type of sink 981 brand produced by the partners of the company PT.Feedmil.This research is a combined quantitative and qualitative research with the technique of collecting observations and interviews with company manager. Analysis tool used is the method of Economic Order Quantity (EOQ) for know your most economical quantities, Reorder Point to determine the level of reordering, and Safety Stock inventory is the amount of feed to know the backup if any time an increase in demand.Document used during August 2018.Based on the results of calculations the researchers did, the following will be conveyed as follows :1. The minimum of inventory (safety stock) of sinking type 981 fish feed is 132 sacks.2. Economic order quantity (EOQ) 981 sink type fish feed reached in the number of economic order is 368 sacks with the frequency of orders 4 times every 7 days a message in one period / month.3. Reorder point if the reamaining inventory amount or close to 264 sack.4. The maximum amount of inventory so that there is no waste of the cost component is 500 sacks. Keywords: Inventory, EOQ, Reorder Point , Safety Stock